Empowerment of Health Cadres in Utilizing Family Medicinal Plants (TOGA) as an Effort to Control Non-Communicable Diseases in the Elderly: Pemberdayaan Kader Kesehatan Dalam Pemanfaatan Tanaman Obat Keluarga (TOGA) Sebagai Upaya Mengontrol Penyakit Tidak Menular Pada Lansia - Basri, Achmad Ali; Maurida, Nurul; Silvanasari, Irwina Angelia (Al-Hijrah Indonesia, 2022)
The aging process results in a decrease in physical and psychological conditions, a decrease in independence, an inability to work and an impact on the non-fulfillment of independence in fulfilling daily basic needs and socializing with the community. Community empowerment efforts to optimize promotive, preventive, curative and rehabilitative for elderly problems need to carry out activities that can support these efforts through the elderly Posyandu, providing support for the elderly and optimizing the use of family medicinal plants for curative efforts for the elderly health problems. This activity aims to apply community-based science and technology for health cadres to manage elderly health problems. The method used in this empowerment is by making health promotion media in the form of leaflets and flipcharts, lectures, demonstrations, providing equipment for processing family medicinal plants, training in cultivating family medicinal plants and training in the production of traditional family medicines which are carried out in Jenggawah Village, the working area of the Jenggawah Health Center. Fifty health cadres attended empowerment participants. Pretest results obtained good knowledge 6%, good attitude 5%, good behavior 3%. After the community service activities were conducted, the post-test scores for good knowledge were 68%, good attitudes were 74%, and good behavior was 62%. So it can be concluded that there has been an increase in knowledge and skills in managing elderly health problems, especially non-communicable diseases, and an increase in cadres’ ability to process herbal ingredients. Suggestions that can be given are that cadres need to apply the knowledge and skills acquired in their daily activities and when implementing the elderly Posyandu.